Essentials of Restenosis For the Interventional Cardiologist - Duckers, Henricus J.; Nabel, Elizabeth G.; Serruys, Patrick W. (Contemporary Cardiology, 2007)
Essentials of Restenosis provides the practicing cardiologists and biologists an elaborate review of the current advances in the field. Authors explore the process of restenosis from bench to bedside, encompassing in equal detail the newest scientific findings of the biological mechanisms as well as the progression in development of diagnostics and treatments. The volume also provides the reader with a basic understanding of the biological process and the latest diagnostics and treatments of the disease, with an up-to-date detailed discussion of the most important recent findings. Leading interventional cardiologists, including Patrick Serruys, Eric Topol, David Holmes, Thomas Luscher and others provide the gold-standard reference on the treatment of restenosis (coronary artery blockage) for interventional cardiologists. Dr. Serruys, who pioneered the use of drug-eluting stents, and other pioneers in the field cover everything from non-invasive imaging, to eluting stents, to brachytherapy through to the latest molecular biology-based treatments including antisense, stem cells and gene therapy, making this an essential reference for all interventional cardiologists. Thorough chapters discuss the current understanding on the pathophysiology, molecular and genetic base, and methods of diagnosis of restenosis, and present the current state-of-the-art management, including pharmacotherapy and interventional percutaneous approaches using brachytherapy, gene therapy and drug eluting stent technology. All this makes Essentials of Restenosis an excellent handbook for introducing new intervention cardiologists, vascular biologists, and medical students into the subject. This text provides the reader with a complete overview of the basic and applied knowledge of restenosis, leading to better insight and decision-making in clinical practice.